Maternal Childhood Maltreatment History and Child Behavior Problems: Developmental Patterns and Mediation via Maternal Depressive Symptoms and Parenting Behavior. (May 2023) - Harris, Madeleine; MacMillan, Harriet; Mepham, Jennifer; Joshi, Divya; Wekerle, Christine; Atkinson, Leslie; Gonzalez, Andrea
Maternal exposure to childhood maltreatment (CM) is associated with offspring behavioral problems; however, little work has examined these associations longitudinally across child development. This study examined the effects of maternal history of CM on trajectories of child internalizing and externalizing behavior measured from toddlerhood to preschool, and the role of maternal depressive symptoms and parenting behavior as potential mediators. Participants included 115 mother–child dyads recruited from a hospital maternity ward. Maternal CM was measured at 3-months postpartum. At 18, 36, and 60 months, maternal depressive symptoms and child behavior were assessed via maternal report and parenting behavior was assessed through direct observation. Findings indicated that children of mothers exposed to CM demonstrated poorer trajectories of problem behavior across early childhood. Maternal depressive symptoms mediated the relation between CM and children's internalizing problems. Findings highlight the importance of screening for maternal depressive symptoms and early intervention for maternal and child mental health.